Preparation, microstructure, properties and foaming mechanism of a foamed ceramics with high closed porosity. Issue 9 (15th June 2019) - Li, Xiangming; Zheng, Mengyao; Li, Rui; Yuan, Guojian; Zhou, Guangyou; Zhu, Xiaotao; Ren, Guina
Abstract: Foamed ceramics with high closed porosity are prepared by the direct foaming method. The foamed ceramics prepared from a green body with a weight ratio of quartz, calcium carbonate, talc and silicon nitride of 63.0:13.5:13.5:10.0 at 1200 °C have a uniform internal microstructure with many well–distributed pores that are independent of each other, relatively high compressive strength of 6.9 MPa and high closed porosity of 85%. Almost all of the pores in the foamed ceramics are closed because of the sealing of the continuous dense surface of the foamed ceramics. During sintering at 1200–1250 °C, the quartz and oxidation–derived amorphous silica are in a molten state and soon melt into a whole, the outer oxygen with relatively small atomic volume can still react with silicon nitride grains after diffusing inwards through the molten phase, while the oxidation–derived nitrogen with relatively large atomic volume could hardly diffuse outwards through the molten phase but aggregates at where it generated in the samples which is the reason resulting in volume expansion of the samples like the slow inflation of a balloon.